Modeling Neurovascular Disorders and Therapeutic Outcomes with Human-Induced Pluripotent Stem Cells - Bosworth, Allison M.; Faley, Shannon L.; Bellan, Leon M.; Lippmann, Ethan S. (Frontiers in Bioengineering and Biotechnology, 2018)
The neurovascular unit (NVU) is comprised of neurons, astrocytes, pericytes, and endothelial cells that form the blood-brain barrier (BBB). The NVU regulates material exchange between the bloodstream and brain parenchyma, and its dysfunction is a primary or secondary cause of many cerebrovascular and neurodegenerative disorders. As such, there are substantial research thrusts in academia and industry towards building NVU models that mimic endogenous organization and function, which could be used to better understand disease mechanisms and assess drug efficacy. Human pluripotent stem cells (hPSCs), which can self-renew indefinitely and differentiate to almost any cell type in the body, are attractive for these models because they can provide a limitless source of individual cells from the NVU. In addition, human induced pluripotent stem cells (iPSCs) offer the opportunity to build NVU models with an explicit genetic background and in the context of disease susceptibility. Herein, we review how iPSCs are being used to model neurovascular and neurodegenerative diseases, with particular focus on contributions of the BBB, and discuss existing technologies and emerging opportunities to merge these iPSC progenies with biomaterials platforms to create complex NVU systems that recreate the in vivo microenvironment.